Pengaruh Produk Domestik Bruto, Tingkat Suku Bunga, Inflasi, dan Pertumbuhan Ekonomi terhadap Foreign Direct Investment di Asean - Septian Abdul Manan; Siti Aisyah (Ekonomis: Journal of Economics and Business, 2023)
Economic development is one of the most important keys to increase government revenue, one example is with foreign direct investment (FDI). The purpose of this study was to examine the effect of variables gross domestic product, interest rates, inflation, and economic growth on Foreign Direct Investment (FDI). Panel data regression was used as a research method in the 2018-2021 time range in several countries such as Indonesia, Malaysia, Thailand, and Vietnam. The results of the study stated that variable interest rates and inflation affect FDI. On the other hand, Gross Domestic Product (GDP) and economic growth variables have no effect on FDI.